Cristofisiologismo dos evangélicos na política brasileira: as estratégias e movimentações das Assembleias de Deus no Brasil e Imperatriz no campo político - Bezaliel Alves Oliveira Junior; Rímila Queiroz de Araujo (Das Amazônias)
This essay is part of an investigation developed by the authors, and which relates to the theme of intersections and border crossings between religious and political spaces in Brazil. The main focus being the analysis of the careers, trajectories and perceptions of religious agents of the Igreja Assembleia de Deus de Imperatriz (IEADI), who have become known for their investment and/or occupation of elective positions in recent years. As a methodological resource, a Bibliographic Review was adopted with authors from historiography as well as sociology, establishing an interdisciplinary discussion and Oral History as an instrument for understanding the visions and narratives that correspond to the subjects/groups analyzed based on the conceptions of Amado; Ferreira (2006) and Delgado (2003), whose propositions deal with the relevance of orality as a strategy in the field of history to perceive the reports and the link between history and memory and how religious issues receive a strong incidence of this resource as sources to be researched. Understanding the connection between history and sociology by envisioning the place of discourse of the clashes and disputes present in the religious field, as stated by Pierre Bourdieu (2007), is extremely necessary. The spatial and temporal scope defined in the work in question focuses on a reality in which the developments around the singularities and characteristics of IEADI typify how the sacred goes beyond a scenario strictly circumscribed within the scope of faith and therefore manifests itself and signals that its process of reaching extends to plural socio-historical strata.